1999
DOI: 10.1017/s0033291798008137
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in the effects of bereavement-related psychological distress in health outcomes

Abstract: The results suggest that there are gender differences in the levels of psychological symptoms resulting from bereavement and in their effects on subsequent mental and physical health for widows and widowers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
156
6
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 208 publications
(173 citation statements)
references
References 21 publications
9
156
6
2
Order By: Relevance
“…Complicated grief, a well-defined syndrome of grief manifestations persisting >6 months [24,25], occurs in ∼10% of bereaved relatives [26,27] and adversely affects quality of life [25,[28][29][30][31]. The persistent manifestations may include intense yearning for the deceased, a sense of disbelief regarding the death, anger, bitterness, intrusive preoccupying thoughts of the deceased, avoidance of reminders of the loss and difficulty in moving on with life [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Complicated grief, a well-defined syndrome of grief manifestations persisting >6 months [24,25], occurs in ∼10% of bereaved relatives [26,27] and adversely affects quality of life [25,[28][29][30][31]. The persistent manifestations may include intense yearning for the deceased, a sense of disbelief regarding the death, anger, bitterness, intrusive preoccupying thoughts of the deceased, avoidance of reminders of the loss and difficulty in moving on with life [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Age has also yielded conflicting results: some studies have shown younger bereaved subjects being more likely to develop MDD [20,30] , while others have reported an absence of association of age with MDD [21-23, 28, 37, 38] . Women have also been shown to be more likely [24,38,39] or as likely to develop MDD [20-23, 28, 30, 37, 40] compared to men after the loss of a loved one. These differences may be due to varying study designs and sample populations.…”
Section: Predictors Of Major Depression In Bereavementmentioning
confidence: 99%
“…Widows have poorer physical health and greater unintentional weight loss over a three-year follow-up (Wilcox et al 2003) and widows experiencing traumatic grief are at greater risk of long-term ill health such as cancer or heart attack (Chen et al 1999). Health service use may increase significantly with complicated grief reactions (Ray & Prigerson 2006).…”
Section: Complications Of Griefmentioning
confidence: 99%